2018
DOI: 10.1002/ccr3.1490
|View full text |Cite
|
Sign up to set email alerts
|

Sevoflurane improves respiratory mechanics and gas exchange in a case series of infants with severe bronchiolitis‐induced acute respiratory distress syndrome

Abstract: Key Clinical MessageThis report describes the successful use of a new intervention to improve respiratory mechanics and gas exchange in a relatively homogeneous group of infants with severe bronchiolitis‐induced PARDS after failure of conventional treatment. These results may open a new interesting area of research and management for PARDS patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 27 publications
1
4
0
Order By: Relevance
“…Hence, we cannot exclude that the early decrease in blood pressure was the result of a potential oversedation caused by the combination of isoflurane and the intravenous sedatives which had not yet been reduced sufficiently or had long half-lifes. Vasopressors had to be started or increased in 93% of the children, a fact that is in line with Nacoti et al 22 Moreover, we observed 2 clinically relevant episodes of hypotension that were clearly related to isoflurane and required immediate therapy and discontinuation of LTIS in 1 patient. Heart rate also decreased regularly, but to a lesser extent.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Hence, we cannot exclude that the early decrease in blood pressure was the result of a potential oversedation caused by the combination of isoflurane and the intravenous sedatives which had not yet been reduced sufficiently or had long half-lifes. Vasopressors had to be started or increased in 93% of the children, a fact that is in line with Nacoti et al 22 Moreover, we observed 2 clinically relevant episodes of hypotension that were clearly related to isoflurane and required immediate therapy and discontinuation of LTIS in 1 patient. Heart rate also decreased regularly, but to a lesser extent.…”
Section: Discussionsupporting
confidence: 89%
“…Bronchospasm requiring specific medication was observed in 2 of 23 children by Mencia et al, 15 and 2 patients had seizures related to the inhalative sedation. 17,22 Neither bronchospasm nor seizures were observed in our study cohort. Based on the timedependent increase of fluoride in the blood reported by Arnold et al, 20 we also analyzed plasma fluoride levels in some of our patients.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…(Hornuss et al 2010) Sevoflurane improved pulmonary mechanics and gas exchange in a case series of infants with severe bronchiolitis and acute respiratory distress syndrome. (Nacoti et al 2018) In short, a controlled clinical trial of isoflurane or sevoflurane when intubated COVID-19 patients are sedated is warranted.…”
mentioning
confidence: 99%